2021 pioneering investigator issue: mesoporous polyetherimide thin films via hydrolysis of polylactide-b-polyetherimide-b-polylactide. Issue 27 (4th June 2021) - Guo, Dong; Riet, Jocelyn; Khan, Assad; Guo, Yichen; Xu, Zhen; Liu, Tianyu; Liu, Guoliang
Abstract : Hydrolyzing polylactide- b -polyetherimide- b -polylactide triblock copolymers produces mesoporous polyetherimide thin films with an average pore width of 24 nm. Abstract : Mesoporous polyetherimides are important high-performance polymers. Conventional strategies to prepare porous polyetherimides, and polyimide in general, are based on covalent organic framework or thermolysis of sacrificial polymers. The former produces micropores due to intrinsically crosslinked microstructures, and the latter results in macropores because of a blowing effect by the sacrificial polymers. The preparation of mesopores remains a challenge. Here we have prepared mesoporous polyetherimide films by hydrolyzing polylactide- b -polyetherimide- b -polylactide (AIA). Controlled by molecular weight and volume fraction of polylactide in AIA, the porous films exhibit an average pore width of 24 nm. The mesoporous polyetherimide films exhibit a storage modulus of ∼1 GPa at ambient temperatures. This work advances the chemistry of high-performance polymers and provides an alternative strategy to prepare mesoporous polymers, enabling potential use as high-performance membranes for separation, purification, and electrochemistry.